2007
DOI: 10.1108/03074350810838226
|View full text |Cite
|
Sign up to set email alerts
|

Price and trading volume reactions to index constitution changes

Abstract: Purpose -US studies show significant price effects when shares enter or leave an index during index revisions. Studies on other markets generally yield similar results with smaller price reactions. This study aims to examine the price effects resulting from revisions to the Australian S&P/ASX 100 and 300 indices. Design/methodology/approach -The event study methodology is used to examine abnormal price and volume effects around the announcement dates and implementation dates of index revisions. Findings -In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
5
2
Order By: Relevance
“…(Yu et al, 2015) found that the influencing factor was due to the increased attention (awareness) of analysts on the company's shares so that in the end it had an impact on increasing company liquidity. (Qiu and Pinfold, 2007) in their research on companies that enter and exit the S&P Index (ASX100 and ASX300) in Australia show that there is generally no market reaction to changes in the list of companies (in and out) of the S&P Index.…”
Section: Efficient Market Hypothesismentioning
confidence: 99%
“…(Yu et al, 2015) found that the influencing factor was due to the increased attention (awareness) of analysts on the company's shares so that in the end it had an impact on increasing company liquidity. (Qiu and Pinfold, 2007) in their research on companies that enter and exit the S&P Index (ASX100 and ASX300) in Australia show that there is generally no market reaction to changes in the list of companies (in and out) of the S&P Index.…”
Section: Efficient Market Hypothesismentioning
confidence: 99%
“…Starting in the mid-1990s, some studies began examining other indices (see, e.g., Beneish & Gardner, 1995;Chen, 2006) and in recent years researchers have started to study indices of developed markets outside the U.S. (see, e.g., Liu, 2000;Masse et al, 2000;Masse, 2007;Qiu & Pinfold, 2008). However, research on indices of emerging markets is still in its early stages (see, Bildik & Gulay, 2008;Elayan et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Lee et al (2008) document significant abnormal returns for S&P 500 additions during the post-trading session after the announcement. Other studies that find abnormal post-announcement returns include Harris and Gurel (1986), Goetzmann andGarry (1986), Shleifer (1986), Jain (1987), and Beneish and Whaley (1996) for the S&P 500, Petajisto (2011) and Chang et al (2014) for the Russel2000, Deininger et al (2000) for the German DAX and MDAX, Doeswijk (2005) for the AEX index, Chakrabarti et al (2005) for international MSCI indices, Liu (2006) and Liu (2011) for the Nikkei225, Mazouz and Saadouni (2007) and Mase (2007) for the FTSE100, Qiu and Pinfold (2007) for the ASX300, and Yun and Kim (2010) for the KOSPI 200. Similar to the German DAX, many of these indices are based on a publicly available rule-based methodology.…”
Section: Introductionmentioning
confidence: 99%